2013
DOI: 10.1111/pcn.12036
|View full text |Cite
|
Sign up to set email alerts
|

Month of birth and mood seasonality: A comparison between countries in the northern and southern hemispheres

Abstract: Aims A previous study has reported a significant month‐of‐birth effect on mood seasonality in the northern hemisphere. Higher mood seasonality was observed for university students born during spring or summer months (long photoperiod) compared to those born during autumn or winter months (short photoperiod). The aim of this study was to test the hypothesized photoperiod effect by comparing the correlation between month of birth and mood seasonality in two countries located at the opposite poles of the terrestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
1
7
0
2
Order By: Relevance
“…In line with previous findings 9,11 , we observed a main effect for gender on mood seasonality. These congruent findings indicate that women tend to experience greater mood seasonality than men, and that the current treatments for sufferers of mood disorders (such as SAD) may have differing effects for men and women.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…In line with previous findings 9,11 , we observed a main effect for gender on mood seasonality. These congruent findings indicate that women tend to experience greater mood seasonality than men, and that the current treatments for sufferers of mood disorders (such as SAD) may have differing effects for men and women.…”
Section: Discussionsupporting
confidence: 82%
“…A significant overall month of birth effect was observed only for male participants (regardless of country), with those born in April or August having higher mood seasonality than those born in February. This and other studies have also observed significant gender differences, with female participants showing higher mood seasonality than males 9,11 . Due to the geographic location of the findings reviewed above, it would be necessary to test the robustness of these results using more samples from countries in the Sou thern Hemisphere.…”
Section: Introductionmentioning
confidence: 49%
See 3 more Smart Citations